Analysis of the Effect of Relaxation Techniques on Sleep Quality in Patients with Sleep Disorders - Trihandayani, Yani (International Journal of Nursing and Midwifery Research, 2024)
Sleep disorders, including insomnia, obstructive sleep apnea, and restless legs syndrome, significantly impact health and quality of life. Non-pharmacological interventions, such as relaxation techniques, have emerged as promising approaches to enhance sleep quality without the risks associated with medication. This study aims to evaluate the efficacy of various relaxation methods mindfulness meditation, progressive muscle relaxation, guided imagery, and deep breathing exercises in improving sleep outcomes among patients with sleep disorders. A randomized controlled trial design was employed, with participants randomly assigned to either an experimental group receiving specific relaxation techniques or a control group. Objective measures of sleep quality, including sleep onset latency, total sleep time, wake after sleep onset, and subjective assessments using validated scales like the Pittsburgh Sleep Quality Index (PSQI) and Insomnia Severity Index (ISI), were utilized. Preliminary results indicate significant improvements in sleep parameters among participants in the experimental group compared to controls. Reductions in insomnia severity, enhanced sleep continuity, and improved subjective sleep satisfaction were observed following the intervention period. Secondary outcomes, including daytime functioning and quality of life, also showed positive trends among participants receiving relaxation techniques.